Evaluation of Fasting Capillary Glucose and Fasting Plasma Glucose as Screening Tests for Diabetes and Prediabetes among Adults in a Semi-Urban Area in the Kathmandu District, Nepal (Nepal Medical College Journal, 2019)
The natural history of type 2 diabetes includes a preceding period of impaired fasting glucose or impaired glucose tolerance which is referred to as prediabetes. During the asymptomatic phase of prediabetes, an estimated 20-30% of persons may develop complications like retinopathy, cardiovascular disease, neuropathy and nephropathy. Screening and lifestyle management may help to delay or arrest progression to diabetes. In primary care settings, point of care devices that measure glucose in capillary blood can be used for diagnosis of diabetes. This study was carried out to evaluate the performance of fasting capillary glucose (FCG) and fasting plasma glucose (FPG) measurement in screening for diabetes and prediabetes among adults in a semi-urban community in the Kathmandu district of Nepal. An observational, cross-sectional study design was used and FCG, FPG performance was evaluated by the 2-hour plasma glucose levels (2-hr PG) following Oral glucose tolerance test (75g glucose) using WHO 1998 criteria. Linear regression was performed to assess correlation co-efficient (r) between FPG, FCG and 2 hr PG. Bland Altman plot and Receiver operator characteristic (ROC) curves were constructed to assess concordance, measure ROC AUC and determine sensitivity and specificity of the measurements at recommended cut-off values for identifying diabetes and prediabetes. Among the study participants (n=162), 104 were female and 58 were male. Prevalence of undiagnosed diabetes and prediabetes was 4.32% (95% CI 1.75% to 8.70%) and 7.14% (95% CI 3.89% to 12.58%). Strong positive correlation was seen between FPG and FCG (Spearman’s r 0.67). FPG & FCG had a moderate positive correlation (r = 0.49 & 0.45) with 2 hr PG levels (p